Exertion of Cultures and Hegemonic Power in Banyuwangi: The Midst of Postmodern Trends - Ikwan Setiawan; Albert Tallapessy; Andang Subaharianto (Karsa: Journal of Social and Islamic Culture, 2017)
This article aims to criticize the incorporation and commodification of Using cultures undergone by Abdullah Azwar Anas in Banyuwangi, East Java. To answer the problem, we analyze primary data from our field research and secondary data from online media related to AAA’s efforts to incorporate, articulate, and commodify Using cultures into various carnival programs (2011-2017) by applying theories of commodification, postmodernism, and hegemony. The result of this study shows that, driven by his desire to promote Using cultures globally in the midst of postmodern trends, since 2011 the government of Banyuwangi has created many carnivals and festivals, such as “Banyuwangi Ethno Carnival”, “Banyuwangi Beach Jazz Festival”, “Parade Gandrung Sewu”, and other various programs. Economically, the programs are idealized to support the regional economic growth through tourism activities, both for domestic and international tourists, by displaying traditional expressions with new styles and performances. Politically, the carnivals and festivals can support AAA efforts to negotiate its political concern in order to produce consensus.Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i1.1118